1993
DOI: 10.1161/01.cir.88.3.1083
|View full text |Cite
|
Sign up to set email alerts
|

Influence of implantable cardioverter-defibrillators on the long-term prognosis of survivors of out-of-hospital cardiac arrest.

Abstract: BACKGROUND Survivors of out-of-hospital cardiac arrest not associated with acute myocardial infarction are at high risk for recurrent cardiac arrest and sudden cardiac death. The impact of the implantable cardioverter-defibrillator on long-term prognosis in these patients is uncertain. METHODS AND RESULTS Three hundred thirty-one survivors of out-of-hospital cardiac arrest (age, 56 +/- 13.7 years) underwent electrophysiologically guided therapy. Implant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
44
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(47 citation statements)
references
References 35 publications
2
44
1
Order By: Relevance
“…16 However, there have been very few detailed reports on the incidences of the recurrence of lethal arrhythmias and the efficacy of use of an implantable cardioverter defibrillator for preventing sudden cardiac arrest in OHCA patients during a long-term follow-up. [18][19][20][21] Ruppel et al reported that among 40 patients who had survived an episode of ventricular fibrillation and subsequently received an implantable cardioverter defibrillator, 41 episodes of ventricular arrhythmias were documented in 13 patients (33%). 22 In the present study, we also found implantable cardioverter defibrillator discharge in 2 (22%) of the 9 survivors.…”
Section: Improvement In Long-term Prognosis Of Ohca Patientsmentioning
confidence: 99%
“…16 However, there have been very few detailed reports on the incidences of the recurrence of lethal arrhythmias and the efficacy of use of an implantable cardioverter defibrillator for preventing sudden cardiac arrest in OHCA patients during a long-term follow-up. [18][19][20][21] Ruppel et al reported that among 40 patients who had survived an episode of ventricular fibrillation and subsequently received an implantable cardioverter defibrillator, 41 episodes of ventricular arrhythmias were documented in 13 patients (33%). 22 In the present study, we also found implantable cardioverter defibrillator discharge in 2 (22%) of the 9 survivors.…”
Section: Improvement In Long-term Prognosis Of Ohca Patientsmentioning
confidence: 99%
“…[1][2][3] Patients with end-stage heart failure listed for cardiac transplantation are at high risk of sudden cardiac death while on the waiting list. [4][5][6] Of all deaths in patients on the waiting list, Յ70% occur suddenly.…”
mentioning
confidence: 99%
“…However, several clinical studies [1][2][3] have demonstrated that the annual incidence of sudden death in patients with ICDs is presumed to be approximately 2%. Sudden death cannot be completely avoided even after ICD therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Takashi Kurita, 1 MD, Shigeyuki Ueda, 2 MD, Hideo Okamura, 2 MD, Takashi Noda, 2 MD, Kazuhiro Satomi, 2 MD, Kazuhiro Suyama, 2 MD, Wataru Shimizu, 2 MD, Naohiko Aihara, 2 MD, Shunichi Miyazaki, 1 MD and Shiro Kamakura, 2 MD,…”
Section: Destructive Device Removal -Sparks and Deletion Of Therapy Hmentioning
confidence: 99%